Vipers of the Middle East: A Rich Source of Bioactive Molecules - Mohamad Rima; Seyedeh Maryam Alavi Naini; Marc Karam; Riyad Sadek; Jean-Marc Sabatier; Ziad Fajloun (Molecules, 2018)
Snake venom serves as a tool of defense against threat and helps in prey digestion. It consists of a mixture of enzymes, such as phospholipase A2, metalloproteases, and l-amino acid oxidase, and toxins, including neurotoxins and cytotoxins. Beside their toxicity, venom components possess many pharmacological effects and have been used to design drugs and as biomarkers of diseases. Viperidae is one family of venomous snakes that is found nearly worldwide. However, three main vipers exist in the Middle Eastern region: Montivipera bornmuelleri, Macrovipera lebetina, and Vipera (Daboia) palaestinae. The venoms of these vipers have been the subject of many studies and are considered as a promising source of bioactive molecules. In this review, we present an overview of these three vipers, with a special focus on their venom composition as well as their biological activities, and we discuss further frameworks for the exploration of each venom.